Choice of international branch campus: a case study (UCL Press, 2023)
International branch campuses (IBCs) are becoming an alternative to domestic higher education institutions. Through interviews with Chinese undergraduates at a British IBC in China, this article examines the choice of a British IBC, using a combined model as the conceptual framework. It finds that the factors both affecting college choice and impacting study abroad influence the choice to study at an IBC, because of the nature of IBCs as foreign presences in the host countries. Academic achievement and supply of resources are necessary but not sufficient conditions for the choice of IBC. Further, students choose IBCs over other universities with similar entry requirements because of their capital and habitus, represented by their socio-economic status. Both students and their parents hope to leverage their accumulated cultural capital to reproduce their cultural capital, or to convert their existing economic capital into cultural capital. Moreover, social capital affects the choice to study at an IBC, and its impacts depend on the volume, strength and quality of the social network. Parents are the most influential persons, impacting the choice of IBC with their capital. Last, institutional characteristics, particularly as a gateway to studying abroad, attract students to study at IBCs.